Biological Activity of Quinazolone-4 Derivatives - Muzaffarov Adil Akhmadbekovich,; Muydinov Muslimbek Makhsutali ugli, (American Journal of Biology and Natural Sciences, 2025)
This work is devoted to the study of the biological activity of 2-phenyl quinazolone-4 derivatives. The work presents data on the study of the effect of 2-phenyl quinazolone-4 derivatives on soybean yield. Optimum concentrations of the solution for soaking soybean seeds before sowing are determined.